Co-designing the future: Integrating social transition and compliance for sustainable mine closures - O. Koatlhai (The Southern African Institute of Mining and Metallurgy, 2025)
Mine closures have traditionally prioritised environmental rehabilitation, often overlooking the deep socio-economic disruptions that follow, particularly in mining-dependent communities. This paper argues that mine closure should not mark the end of prosperity but rather the beginning of a sustainable transition. The coproduction model, which integrates community participation, governance, and economic planning, offers a transformative approach to closure planning. Drawing on case studies from Ghana, Zambia, and Indonesia, this research examines the successes and failures of past closures, highlighting the critical role of stakeholder engagement, skills development, and economic diversification. By incorporating emerging technologies such as AI-driven economic forecasting, blockchain for governance transparency, and decentralised finance (DeFi) models, mining companies can ensure a just and sustainable post-mining future. This study challenges outdated closure models and presents a forward-looking strategy that sees mine closure not as an endpoint, but as a catalyst for social resilience and economic transformation. It underscores the need for policy reforms, stronger governance, and investment in alternative industries to prevent mining towns from becoming economic wastelands. By shifting the paradigm from remediation to regeneration, this research calls for a new era of mine closure planning that puts people and prosperity at its core.